Simulation and Analysis of PEM Fuel Cell System using MATLAB - Mohd Hamzah, Syasya Nurmaisarah (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The proton exchange membrane fuel cell is one of the renewable energy technologies that has become an essential technology to create electricity that is hugely beneficial for human activities. It is one of the technologies that has contributed to the rise in the popularity of renewable energy. The study’s observation is to design a model and simulate the PEM fuel cell system by using three different electrical loads. The proton exchange membrane fuel cell (PEMFC) uses the chemical process to generate energy from hydrogen and oxygen. PEMFC stack modelling aims to establish a foundation for the efficient and effective design of fuel cell systems. For modelling, it may be described by the structure of the PEMFC as well as the working principle. The open-circuit voltage of the PEMFC may be calculated using the Nernst equation in conjunction with several voltage drops determined from the polarisation curve of the PEMFC. MATLAB may be used in the construction of a PEMFC model. The MATLAB/Simulink programme simulates the PEMFC system, which produces the necessary analysis. Fuel cells are able to be fuelled by combinations of hydrogen and oxygen. The construction of an infrastructure that is both secure and efficient in terms of cost is going to be necessary to make use of hydrogen both as a fuel and as a carrier for energy. The simulation results in this project reveal the amount of power generated and energy produced by the PEMFC system, the efficiency of the PEMFC system, and the amount of hydrogen used by the fuel cell.